2013
DOI: 10.3177/jnsv.59.161
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Vitamin D Deficiency in European Adolescents: The HELENA Study

Abstract: Adolescence is a critical life-stage period characterised by rapid growth and development. Low circulating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 39 publications
(38 reference statements)
6
23
1
1
Order By: Relevance
“…Indeed, it has been shown previously that a consistent decline in physical activity is found over the school age years, with males decreasing about 2.7% per year and females decreasing about 7.4% per year [31]. Consistent with previous studies [5], [27], [28], [29], [30], [32], [33], [34], [35], gender and BMI each has an independent effect on serum vitamin D levels in the current study. It has been demonstrated that the prevalence of physical inactivity is higher in girls than boys and is higher in obese children than their normal-weight peers [31].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it has been shown previously that a consistent decline in physical activity is found over the school age years, with males decreasing about 2.7% per year and females decreasing about 7.4% per year [31]. Consistent with previous studies [5], [27], [28], [29], [30], [32], [33], [34], [35], gender and BMI each has an independent effect on serum vitamin D levels in the current study. It has been demonstrated that the prevalence of physical inactivity is higher in girls than boys and is higher in obese children than their normal-weight peers [31].…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that the prevalence of vitamin D deficiency and insufficiency was highest in winter. Previous studies have also reported that the serum 25(OH)D concentration is lower in winter than in summer [29,30], which might because people are lack of enough sunlight expose and spent less time on outdoor exercise in a cold weather, and vitamin D supplementation is not available [31]. …”
Section: Discussionmentioning
confidence: 99%
“…One of the first studies showed a significant association between excessive daytime sleepiness and serum values of 25OHD <20 ng/mL only in black individuals (McCarty et al 2012). Valtueña et al (2013) found that lower levels of 25OHD concentrations were associated with shorter sleep duration (<8 h) in female teenagers. In this study, sleep duration was assessed by self-administered questionnaires, which only provide subjective information about the sleep pattern of subjects.…”
Section: Vitamin D and Sleepmentioning
confidence: 99%